Hubungan Perawatan Lensa Kontak Dengan Penyakit Mata Yang Ditimbulkan Oleh Lensa Kontak - Handini, Wahjoe (Pena Medika Jurnal Kesehatan, 2017)
Emmetropia is a condition in which the parallel beam of an eyeball refracted by the refractory medium is precisely diretine. In this case patients use contact lenses because they want to follow the present trend and want to look more attractive. In contact lens users should be with more complicated treatments that are not in accordance with established procedures, because otherwise will cause eye disease. This study aims to determine the relationship of contact lens care with eye disease caused. Which includes: 1. How to care for contact lenses 2. Time of contact lens 3. Eye disease caused contact lenses. The method of this study is case study described descriptively that describes how the treatment of contact lens cases and cases of disease experienced by the case. From the case of emmetropia was taken one case using contact lenses with treatment that is not in accordance with the standards, among others, on the treatment where the contact lens should be replaced every day once this fluid is not done. The contact lens is selected at 6 months usage, but on the use of 3 months already feel uncomfortable and complained of red eyes, allegedly caused because the care of contact lenses are not done in accordance with the standard.Key words : Emmetropia, contact lense, eye disease, treatment